Implementing of Full Day School in improving the quality of Islamic Religious Education - Elihami Elihami; Abdul Rahman (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This study recognizes an increase in student learning outcomes in Islamic Education lessons by managing the quality of Islamic Education learning. The problems of this study are: 1) How is the process of implementing FDS policies in improving the quality of learning in Islamic Religious Education; 2) Whether through the relation between FDS policy and non-FDS in improving the quality of learning in Islamic Education. 3) What is the relationship between schools that implement FDSs and schools that do not apply FDSs in the Ajatapareng area. The type of research used is a mixed-method in a combination of quantitative and qualitative research. The population in this research is primary schools in the Ajatappareng area with a sample of 50 schools that are FDS and 50 schools that are not FDS. This research aims to improve the quality of student learning outcomes with full-day school policies on Islamic education subjects about human resources and Islamic cultural character by applying the quality of Islamic education learning. The application begins with asking questions, thinking together, and answering; 2) Implementing the FDS policy in photographing the relationship between Islamic Education learning outcomes and the application of FDS in the Ajatapateng Area Elementary Schools to improve student learning outcomes. The results of the strategic goal impact are its application on the independent pathway and the instructional pathway. The main target of education can be adequately achieved; it is necessary to start with an integrated concept through an Islamic approach to elementary school students.